2010
DOI: 10.1111/j.1365-2788.2010.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of intervention effects on challenging behaviour among persons with intellectual disabilities

Abstract: Several biological, psychotherapeutic and contextual interventions effectively reduce challenging behaviours among persons with ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 96 publications
(243 reference statements)
5
58
0
3
Order By: Relevance
“…According to the Wald test included in the HLM approach, this reduction in challenging behavior was statistically significant. These PND and HLM findings correspond to the findings of other meta-analyses published in the domain of persons with disabilities: Behavioral interventions are on average effective in reducing challenging behavior in individuals with disabilities (Didden, Korzilius, van Oorsouw, & Sturmey, 2006;Harvey, Boer, Meyer, & Evans, 2009;Heyvaert, Maes, & Onghena, 2010;Heyvaert, Maes, Van den Noortgate, Kuppens, & Onghena, 2012;Heyvaert, Saenen, Maes, & Onghena, 2014b;Vanderkerken et al, 2013). Nonetheless, based on the likelihood ratio test included in the HLM approach, we found that the intervention effects varied significantly over the participants and studies included in the dataset.…”
Section: Merits and Drawbacks Of The Pnd And The Hlm Approach For Synsupporting
confidence: 89%
“…According to the Wald test included in the HLM approach, this reduction in challenging behavior was statistically significant. These PND and HLM findings correspond to the findings of other meta-analyses published in the domain of persons with disabilities: Behavioral interventions are on average effective in reducing challenging behavior in individuals with disabilities (Didden, Korzilius, van Oorsouw, & Sturmey, 2006;Harvey, Boer, Meyer, & Evans, 2009;Heyvaert, Maes, & Onghena, 2010;Heyvaert, Maes, Van den Noortgate, Kuppens, & Onghena, 2012;Heyvaert, Saenen, Maes, & Onghena, 2014b;Vanderkerken et al, 2013). Nonetheless, based on the likelihood ratio test included in the HLM approach, we found that the intervention effects varied significantly over the participants and studies included in the dataset.…”
Section: Merits and Drawbacks Of The Pnd And The Hlm Approach For Synsupporting
confidence: 89%
“…B. Didden, Korzilius, von Oorsow, Sturmey, 2006;Wood, Cho Blair, Ferro, 2009;Heyvaert, Maes, Onghena, 2010). Die Verfasser kommen zu dem einheitlichen Ergebnis, dass Behandlungsmaß-nahmen dann erfolgreich sind, wenn sie auf einer sorgfältigen funktionalen Verhaltensanalyse beruhen, die Modifikation von Auslösebedingungen sowie die Förderung von alternativen Kompetenzen enthalten und im natürlichen Lebensumfeld des Kindes unter Einbeziehung der Familienmitglieder und Pädagogen durchgeführt werden.…”
unclassified
“…The problem behavior of people with intellectual disabilities 1 (IDs) has a negative impact on their own lives and their environment (Heyvaert, Maes, & Onghena, 2010). It deeply affects their health and quality of life (Langthorne, McGill, & O'Reilly, 2007) as well as their caregivers and families (Emerson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These reviews were generally designed to acknowledge the challenge that problem behavior poses for the professionals and families it affects. In general, these reviews have focused their efforts on evaluating the benefits of functional assessment as well as the effects of different treatments or interventions (e.g., Brosnan & Healy, 2011;Denis, Van den Noortgate, & Maes, 2011;Hanley, Iwata, & McCord, 2003;Heyvaert et al, 2010;Matson & Neal, 2009). For example, Hanley et al (2003) reviewed a total of 277 studies that conducted a functional analysis and identified the relationship between environmental variables and problem behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation